2012
DOI: 10.1016/j.mrfmmm.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of damage-specific DNA polymerases in M13 phage mutagenesis induced by a major lipid peroxidation product trans-4-hydroxy-2-nonenal

Abstract: One of the major lipid peroxidation products trans-4-hydroxy-2-nonenal (HNE), forms cyclic propano- or ethenoadducts bearing six- or seven-carbon atom side chains to G>C≫A>T. To specify the role of SOS DNA polymerases in HNE-induced mutations, we tested survival and mutation spectra in the lacZα gene of M13mp18 phage, whose DNA was treated in vitro with HNE, and which was grown in uvrA(-)Escherichia coli strains, carrying one, two or all three SOS DNA polymerases. When Pol IV was the only DNA SOS polymerase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The role of damage-specific DNA polymerases in mutagenesis induced by HNE was studied in M13mp18 phage by testing survival and mutation spectra in the lacZα gene [ 256 ]. The phage was grown in uvrA(−) Escherichia coli strains, carrying one, two or all three SOS DNA polymerases.…”
Section: Biochemical Targets Of Hnementioning
confidence: 99%
See 1 more Smart Citation
“…The role of damage-specific DNA polymerases in mutagenesis induced by HNE was studied in M13mp18 phage by testing survival and mutation spectra in the lacZα gene [ 256 ]. The phage was grown in uvrA(−) Escherichia coli strains, carrying one, two or all three SOS DNA polymerases.…”
Section: Biochemical Targets Of Hnementioning
confidence: 99%
“…When only Pol II or Pol V were present in host bacteria, phage survival decreased dramatically. Simultaneously, mutation frequency was substantially increased, but exclusively in the strain carrying only Pol V suggesting that induction of mutations by HNE is mainly dependent on Pol V [ 256 ] .…”
Section: Biochemical Targets Of Hnementioning
confidence: 99%
“…The infrequent bypass by Pol II is error-free, while by Pol V is error-prone. Both Pol II and Pol IV can compete with Pol V decreasing mutation rate on HNE-adducted templates [67].…”
Section: Translesion Synthesis Of Exocyclic-dna Adducts and Their Mutmentioning
confidence: 99%
“…The contribution of mismatch repair was excluded [38]. Next studies [67] showed that SOS DNA polymerases may play a role of such a backup system, since Pol IV and Pol II synthesized DNA faithfully on HNE damaged template in E. coli cells (see paragraph 7).…”
Section: Nucleotide Excision Repair and Recombinationmentioning
confidence: 99%
“…This type of peroxidation is a chemical process, in which unsaturated fatty acids of lipids are damaged by free radicals and oxygen under lipoperoxides formation. Lipoperoxides are unstable and decompose to form a wide range of compounds including reactive carbonyl compounds, especially certain aldehydes (malondialdehyde (MDA), 4-hydroxy-2-nonenal (4-HNE)) [15][16][17][18][19][20][21][22] that damage cells by the binding the free amino groups of amino acids of proteins. Consequently, the proteins' aggregates become less susceptible to proteolytic degradation [23][24][25].…”
Section: Introductionmentioning
confidence: 99%